(untitled) (Journal Of Educational and Psychological Researches, 2025)
The research aims to identify emotional suppression among kindergarten female teachers in terms of years of service. The research community was limited to government kindergarten teachers affiliated with the Al-Karkh 1st, 2nd, and 3rd Education Directorates and Al-Rusafa 1st, 2nd, and 3rd in Baghdad Governorate for the academic year 2023-2024. To achieve the research objective, the two researchers developed an emotional suppression scale of 41 items that was administered to a sample of 321 kindergarten female teachers randomly was chosen. The results disclosed that kindergarten teachers have emotional suppression and the ability to postpone responding to have time to think and plan. Female teachers who have years of service from 1–5 and 6–10 have more emotional suppression than female teachers who have years of service from 11–15 and 16 or more. The researchers presented a set of recommendations and suggestions.